2017
DOI: 10.17925/usor.2017.10.01.35
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Resistance Trends Among Ocular Pathogens in the US—Cumulative Results from the Antibiotic Resistance Monitoring in Ocular Microorganisms (ARMOR) Surveillance Study

Abstract: A ntibiotic resistance among ocular pathogens is a public health concern. The multicenter, prospective Antibiotic Resistance Monitoring in Ocular micRoorganisms (ARMOR) study is an ongoing surveillance study designed to report on antibiotic resistance rates and trends among Staphylococcus aureus, coagulase-negative staphylococci (CoNS; includes Staphylococcus epidermidis), Streptococcus pneumoniae, Pseudomonas aeruginosa, and Haemophilus influenzae isolates from ocular infections. Results for more than 4,000 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
82
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(107 citation statements)
references
References 13 publications
21
82
0
4
Order By: Relevance
“…This result is similar to other reports . This supports the importance of administering a high concentration (compared with MIC90 of most causative organisms) of antibiotic directly into the anterior chamber . Studies suggest that topical antibiotics may not add any additional clinical benefit to intracameral injection …”
Section: Discussionsupporting
confidence: 90%
“…This result is similar to other reports . This supports the importance of administering a high concentration (compared with MIC90 of most causative organisms) of antibiotic directly into the anterior chamber . Studies suggest that topical antibiotics may not add any additional clinical benefit to intracameral injection …”
Section: Discussionsupporting
confidence: 90%
“…Monitoring of AMR in bacterial keratitis despite the limitations in antimicrobial susceptibility testing methods in ocular infections, is critical in an era of AMR. These limitations include the use of systemic breakpoints to interpret minimum inhibitory concentration data and the choice of antibiotics tested …”
Section: Introductionmentioning
confidence: 99%
“…These limitations include the use of systemic breakpoints to interpret minimum inhibitory concentration data and the choice of antibiotics tested. 12 Whilst we recognize the limits of antimicrobial susceptibility data for topical ocular therapy, more contemporary data are required to benchmark the current status of AMR in eye samples; to guide empirical antimicrobial therapy; to increase the efficacy of treatment; to reduce the side effects from inappropriate therapy; and to gather data for worldwide AMR surveillance. In the United States, the Antibiotic Resistance Monitoring in Ocular Microorganisms (ARMOUR) study has been annually publishing the susceptibility data for ocular pathogens since 2008.…”
Section: Introductionmentioning
confidence: 99%
“…Rising rates of antibiotic resistance have been a concern especially among S. aureus and CoNS . Five years results of the Antibiotic Resistance Monitoring in Ocular Microorganisms (ARMOR) Surveillance Study conducted in United States showed high rates of methicillin resistance among S aureus 42.2% and CoNS 49.7%. These bacteria would be resistant to cefazolin and cefuroxime of course.…”
Section: Microbial Spectrum Of Endophthalmitis Samples Isolated Betwementioning
confidence: 99%
“…These bacteria would be resistant to cefazolin and cefuroxime of course. Moreover, methicillin resistant staphylococci were more likely to be resistant to other classes of antibiotics including fluoroquinolones, macrolides and aminoglycosides . Sensitivity to moxifloxacin was 88% and 26% in methicillin sensitive and resistant S. aureus respectively, and 86% and 49% in methicillin sensitive and resistant CoNS, respectively.…”
Section: Microbial Spectrum Of Endophthalmitis Samples Isolated Betwementioning
confidence: 99%